Writing With Elbow - Belanoff, Pat (University Press of Colorado, 2002)
Writing with Elbow is a volume written by leading scholars now working in the field of composition who trace their own scholarship to foundational work done by Peter Elbow over the last thirty years. The book is in that sense a celebration. But it is more than that, too. Elbow and process writing are not without their critics, and the essays collected in Writing with Elbow also test him, extend his work, explore his intellectual forebears, address his critics and contexts, and complicate his legacy across a wide range of issues in current composition research and practice. A thoughtful, comprehensive retrospective on Peter Elbow's legacy, Writing with Elbow is a must-read collection for composition scholars, teachers, English educationists, and graduate students.